A Cost-Effective Method for Power Factor ‎Metering Systems ‎ - Al-Naib, ahmed; Hamad , Bashar Abdullah ‎ (International Journal of Electrical and Computer Engineering Systems, 2022)
The power factor (PF) is an important measurement in an AC electrical system that indicates how much power ‎is utilized to accomplish productive work by a load and how much power is consumed. As a result, it’s one of ‎the primary causes of excessive energy costs and power outages. This paper aims to present a simple, cost-‎effective, and accurate PF metering and monitoring system implemented using an Arduino microcontroller with ‎a novel methodology different from other papers. The proposed method is to design the software code instead ‎of using external components of Zero-Crossing Detectors (Z-CDs) for both voltage (V) and current (I) signals, and ‎instead of using Exclusive-OR (X-OR) gates also. Determining the phase-angle and PF in an efficient manner ‎can be useful in many approaches to electrical systems: 1-for synchronization of parallel connections of ‎alternators; 2-for directional protection systems; 3-for PF correction and load management; and 4-for designing ‎watt/energy meters. Using the Proteus 8 Professional (ISIS program), the proposed designed circuit was ‎simulated for more verification. The simulation and experimental findings are presented to validate the ‎proposed metering system’s effectiveness.‎